2008
DOI: 10.1002/jmri.21117
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related and zonal anatomical changes of apparent diffusion coefficient values in normal human prostatic tissues

Abstract: Purpose:To identify age-related changes and differences in the diffusion of water molecules within the prostate, through diffusion-weighted imaging (DWI) of the prostate gland in healthy adult Japanese men. Materials and Methods:A total of 114 healthy male volunteers (mean age, 55 years; range, 24 -81 years) underwent DWI of the prostate with a single-shot echo-planar imaging (EPI) sequence using b-factors of 0 and 1000 seconds/mm 2 . Apparent diffusion coefficient (ADC) values of six locations in the peripher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
35
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 29 publications
(52 reference statements)
7
35
0
Order By: Relevance
“…These differences may be attributed to factors such as the subject's age, size of the static magnetic field from the MR scanner used (1.5 or 3.0 T), b-factor settings, and use of parallel imaging. As in previous reports (12,13,16,18,20,21,30), these findings show that ADC values were higher in normal PZ than in normal CG. In addition, another recent report demonstrated that ADC values increased with age in both PZ and CG (30).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These differences may be attributed to factors such as the subject's age, size of the static magnetic field from the MR scanner used (1.5 or 3.0 T), b-factor settings, and use of parallel imaging. As in previous reports (12,13,16,18,20,21,30), these findings show that ADC values were higher in normal PZ than in normal CG. In addition, another recent report demonstrated that ADC values increased with age in both PZ and CG (30).…”
Section: Discussionsupporting
confidence: 90%
“…As in previous reports (12,13,16,18,20,21,30), these findings show that ADC values were higher in normal PZ than in normal CG. In addition, another recent report demonstrated that ADC values increased with age in both PZ and CG (30). ADC values observed in normal regions in the present study are compatible with those results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, higher field strengths can also introduce more challenges regarding susceptibility effects. The use of higher b values (0 to 1 000 and 2 000 s/mm 2 ) can improve lesion detection at the expense of a lower signal-to-noise ratio (82)(83)(84)(85). Prostate cancer lesions demonstrate hyperintense signal characteristics compared with the healthy peripheral zone on raw DWI, whereas they show a decreased signal intensity relative to healthy peripheral zone on ADC maps (86).…”
Section: Male Pelvis Applicationsmentioning
confidence: 99%
“…DWI has a low signal noise ratio (SNR), but the emergence of high-field-strength magnets, the widespread use of endorectal coils and parallel imaging approaches will yield better SNR and, therefore, better spatial/temporal resolution for DWI. Additionally, the use of higher gradient strengths (e.g., b values of 1 000 to 2 000 s/mm 2 ) improves the performance of DWI for lesion detection (83)(84)(85)97). Moreover, DWI currently stands as the most promising quantitative MRI technique for improving our understanding of the nature of prostate cancer lesions (Fig.…”
Section: Male Pelvis Applicationsmentioning
confidence: 99%